2019
DOI: 10.1038/s41598-019-52328-w
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the sea surface height wavenumber spectrum from altimeter observations

Abstract: In this paper, the zonal and meridional sea surface height (SSH) wavenumber spectra are systematically calculated using along-track and gridded altimeter products, and the slopes of the SSH wavenumber spectra over the mesoscale band, which is defined by the characteristic length scale of mesoscale signals, are estimated. The results show that the homogeneous spectral slopes calculated from the along-track and gridded altimeter datasets have a similar spatial pattern, but the spectral slopes from gridded altime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Both SQG and QG theories predict different exponents for the spectra of KE and SSH, which is an indicative of the region's dynamics. Although spectral slopes over the mesoscale range from along-track altimetry are consistent with the turbulence theories (Vergara et al, 2019;Wang et al, 2019) in highly energetic regions, the reasons for the flatter spectra found in low-energy regions still poses an ongoing debate (Richman et al, 2012;Sasaki et al, 2014;Uchida et al, 2017). In this context, improved theoretical framework should be pursued.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Both SQG and QG theories predict different exponents for the spectra of KE and SSH, which is an indicative of the region's dynamics. Although spectral slopes over the mesoscale range from along-track altimetry are consistent with the turbulence theories (Vergara et al, 2019;Wang et al, 2019) in highly energetic regions, the reasons for the flatter spectra found in low-energy regions still poses an ongoing debate (Richman et al, 2012;Sasaki et al, 2014;Uchida et al, 2017). In this context, improved theoretical framework should be pursued.…”
Section: Discussionmentioning
confidence: 83%
“…Wang et al. (2019) pointed out that these slopes are correlated with eddy kinetic energy (EKE), being steeper when the energy is high. Both studies found regional differences between the spectra, and Vergara et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimation of the SLA spectral slope α is usually a two-step procedure [8], [10], [11], [13], [14]. First, an estimation of the PSD is done.…”
Section: A Conventional Methods For Sla Spectral Slope Estimationmentioning
confidence: 99%
“…To perform a reliable slope estimation, the PSD estimate has to have a variance sufficiently low. Therefore, the widely used spectral method is based on a cumulated (Welch) periodogram which consists of averaging a large number of periodograms of along-track SLA segments [8], [10]- [14]. This PSD averaging determines the spatial and temporal resolution of the resulting slope map, depending on the size of the area in latitude and longitude and on the time period from which the SLA signals are issued.…”
mentioning
confidence: 99%